A method for electron beam printing copper-chromium-niobium heat dissipation shell
The copper-chromium-niobium heat dissipation shell is prepared through electron beam printing, which solves the problems of time-consuming material processing, high waste of raw materials, and high internal stress in traditional manufacturing processes, and achieves a high thermal conductivity and strength heat dissipation shell.
Patent Information
- Application Number
- CN202411834405.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-04
AI Technical Summary
During the manufacturing process, the existing copper-chromium-niobium heat dissipation shells have problems such as time-consuming material processing, large waste of raw materials, large internal stresses of the product, prone to cracks and uneven microstructure.
The copper-chromium-niobium heat dissipation shell is prepared by electron beam printing technology. By preheating the substrate and powder, the electron beam scanning speed and current are controlled, and layer by layer is printed and turned and polished to form a heat dissipation shell with high thermal conductivity and strength.
It reduces waste of raw materials, realizes rapid precipitation and growth of the solid solution phase of chromium niobium, ensures the thermal conductivity and strength of the heat dissipation shell, and reduces internal stress and defects.
Smart Images

Figure CN119747683A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of additive manufacturing, and in particular to a method for electron beam printing a copper-chromium-niobium heat dissipation shell. Background Art
[0002] Copper-chromium-niobium is a highly conductive, high-strength, dispersed-strength copper alloy used to manufacture high-heat flux housings, such as liquid rocket engine combustion devices. However, copper-chromium-niobium heat sink housings are currently mostly produced using subtractive manufacturing processes, which is time-consuming to process and results in a large amount of raw material waste.
[0003] Although there is a method of using 3D printing technology to prepare copper-chromium-niobium alloy shells, due to the low energy absorption rate of copper-chromium-niobium, the copper-chromium-niobium powder cannot be fully melted, the prepared products have a large amount of internal stress, are prone to many cracks, and the microstructure is uneven, with more segregation inside. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a method for electron beam printing a copper-chromium-niobium heat dissipation housing.
[0005] The technical solution of the present invention is: a method for electron beam printing a copper-chromium-niobium heat dissipation housing, comprising the following steps:
[0006] S1. Take 140-270 mesh copper-chromium-niobium powder as printing powder;
[0007] S2, adding printing powder into the building chamber of the electron beam printing device, preheating the substrate and the printing powder, the substrate preheating temperature is 560-600°C, and the preheating time is 25-35s;
[0008] S3, after preheating is completed, printing begins layer by layer. The electron beam scanning speed during printing is 3200-3600 mm / s, the current is 25-35 mA, and the printing layer thickness is 0.05-0.5 mm. After printing is completed, a blank is obtained;
[0009] S4, turning and polishing the blank to obtain a heat dissipation shell.
[0010] Description: The present invention prepares the heat dissipation shell through the electron beam printing process. Compared with the traditional subtractive manufacturing process, it can reduce the waste of raw materials, and the substrate will be maintained at a good temperature during the printing process, so as to achieve the rapid precipitation and growth of the chromium niobium solid solution phase, thereby ensuring the thermal conductivity and strength of the heat dissipation shell.
[0011] Furthermore, in step S4, the powder is preheated by an electron beam before printing each layer, and the current of the preheating electron beam is 45-50 mA.
[0012] Note: Preheating can make the satellite powder and small particle powder sinter together to ensure the printing quality of the heat dissipation shell.
[0013] Furthermore, in step S2, the printing powder is dried at 160-200° C. for 10-14 hours before being added to the building chamber.
[0014] Note: The above drying temperature can fully remove the moisture attached to the printing powder, so that the printing powder has good fluidity.
[0015] Furthermore, in step S4, the turning processing amount is 0.8-1.2 mm.
[0016] Note: Limiting the amount of turning can ensure the surface accuracy of the heat dissipation shell.
[0017] Furthermore, in step S4, a sandblasting process is used during polishing.
[0018] Note: The sandblasting process can be used to remove burrs and other defects on the surface of the heat dissipation shell to ensure the surface accuracy of the heat dissipation shell.
[0019] Further, the printing powder is mixed by 6 to 8 parts of copper-chromium-niobium coarse powder and 2 to 4 parts of modified copper-chromium-niobium fine powder by weight, the particle size of the copper-chromium-niobium coarse powder is 140 to 220 meshes, and the particle size of the modified copper-chromium-niobium fine powder is 220 to 270 meshes. The modification method of the modified copper-chromium-niobium fine powder comprises the following steps:
[0020] S1-1, dissolving copper sulfate in deionized water to obtain a copper sulfate solution; dissolving p-hydroxybenzoic acid in anhydrous ethanol to obtain a p-hydroxybenzoic acid solution; wherein the mass ratio of copper sulfate to deionized water is 1:11-13, and the mass ratio of p-hydroxybenzoic acid to anhydrous ethanol is 1:6-8;
[0021] S1-2, mixing the copper sulfate solution and the p-hydroxybenzoic acid solution in a mass ratio of 1:0.8-1.2, stirring evenly to obtain a mixed solution;
[0022] S1-3, adding ammonia water to the mixed solution, adjusting the pH value of the mixed solution to 7-9, then adding copper, chromium and niobium fine powders to the mixed solution in an amount of 3-5 times its own weight, and heating the mixed solution. During the heating process, the mixed solution is subjected to ultrasonic treatment, the initial frequency of the ultrasonic treatment is 20-25 kHz, and the frequency of the ultrasonic treatment is increased by 1-3 kHz for every 5-10°C increase in the temperature of the mixed solution, until the temperature of the mixed solution reaches 60-70°C, and the temperature is kept for 20-24 hours;
[0023] S1-4. After the ultrasonic treatment is completed, the mixed solution is filtered to obtain solid particles, and the solid particles are washed to obtain modified copper, chromium and niobium fine powder.
[0024] Description: The copper ions and p-hydroxybenzoic acid form a coordination polymer, and the copper chromium niobium fine powder is loaded onto the copper chromium niobium fine powder to modify the copper chromium niobium fine powder. The copper ion / p-hydroxybenzoic acid coordination polymer improves the fluidity of the copper chromium niobium fine powder, and the copper ion / p-hydroxybenzoic acid coordination polymer can be adsorbed onto the copper chromium niobium coarse powder, thereby reducing the pores between the printed powders and increasing the absorption rate of the printed powder for the electron beam, promoting the formation of the molten pool and reducing the cooling rate of the molten pool, so as to form a good interface diffusion during the electron beam printing process and reduce defects in the heat dissipation shell.
[0025] Furthermore, in step S1-3, the mass concentration of the ammonia water is 20-25%.
[0026] Note: The above mass concentration of ammonia water can accurately adjust the pH value, is easy to prepare and safe to use.
[0027] Furthermore, in step S4, during the printing, whenever the temperature of the powder in the electron beam focus area exceeds 1070-1090°C, the electron beam is switched to intermittent irradiation, and when the temperature of the powder in the electron beam focus area is lower than 940-980°C, the electron beam is switched to continuous irradiation.
[0028] Note: The above printing method maintains the printing molten pool at an appropriate temperature by alternating continuous irradiation with intermittent irradiation, avoids cracking caused by excessively high molten pool temperature, and ensures the printing quality of the heat dissipation housing.
[0029] Furthermore, the irradiation time T of the intermittent irradiation and the interval time T of the intermittent irradiation are 1 The following relationship is met:
[0030]
[0031] Among them, m 1 is the mass of modified copper-chromium-niobium fine powder, m is the total mass of printed powder, T 1 The value is 2 to 6 ms.
[0032] Note: Intermittent irradiation through the above relationship can ensure that the printing powder can be fully melted to form a molten pool, and ensure the cooling rate of the molten pool, so as to avoid the molten pool cooling too quickly and causing the gas in the molten pool to not be fully discharged.
[0033] Furthermore, the modified copper-chromium-niobium fine powder and the copper-chromium-niobium coarse powder are mixed with a powder mixer for 8 to 12 hours.
[0034] Note: Limiting the powder mixing parameters can ensure that the modified copper-chromium-niobium fine powder is fully mixed with the copper-chromium-niobium coarse powder, avoiding defects in the heat dissipation shell caused by uneven powder mixing.
[0035] The beneficial effects of the present invention are:
[0036] (1) The present invention prepares the heat dissipation shell by electron beam printing process, which can reduce the waste of raw materials compared with the traditional subtractive manufacturing process. In addition, the substrate will be maintained at a good temperature during the printing process, so that the chromium niobium solid solution phase can be rapidly precipitated and grown, thereby ensuring the thermal conductivity and strength of the heat dissipation shell.
[0037] (2) The present invention forms a coordination polymer with copper ions and p-hydroxybenzoic acid, and loads it onto copper-chromium-niobium fine powder to modify the copper-chromium-niobium fine powder, thereby improving the fluidity of the copper-chromium-niobium fine powder. The copper ion / p-hydroxybenzoic acid coordination polymer can be adsorbed onto the copper-chromium-niobium coarse powder, thereby reducing the pores between the printed powders and improving the absorption rate of the printed powders for the electron beam, thereby promoting the formation of a molten pool and reducing the cooling rate of the molten pool, so as to form a good interface diffusion during the electron beam printing process and reduce defects in the heat dissipation housing. DETAILED DESCRIPTION
[0038] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.
[0039] Embodiment 1: A method for electron beam printing a copper-chromium-niobium heat dissipation housing, comprising the following steps:
[0040] S1. Take 140-270 mesh copper-chromium-niobium powder as printing powder;
[0041] S2, adding the printing powder into the building chamber of the electron beam printing device, preheating the substrate, the substrate preheating temperature is 580°C, and the preheating time is 30s; before adding the printing powder into the building chamber, the printing powder is dried at 180°C for 12h;
[0042] S3. After preheating, printing begins layer by layer. The electron beam scanning speed during printing is 3400 mm / s, the current is 30 mA, and the printing layer thickness is 0.15 mm. After printing, a blank is obtained. The powder is preheated by an electron beam for each layer of printing. The current of the preheating electron beam is 45-50 mA. The focus offset during printing is 15, and the line offset is 0.125.
[0043] S4. Turn and polish the blank to obtain a heat dissipation shell; the turning processing amount is 1 mm, and the sandblasting process is used for polishing.
[0044] Example 2: This example is basically the same as Example 1, except that the substrate preheating temperature is 560°C.
[0045] Example 3: This example is basically the same as Example 1, except that the substrate preheating temperature is 600°C.
[0046] Embodiment 4: This embodiment is basically the same as Embodiment 1, except that the electron beam scanning speed during printing is 3200 mm / s.
[0047] Embodiment 5: This embodiment is basically the same as Embodiment 1, except that the electron beam scanning speed during printing is 3600 mm / s.
[0048] Example 6: This example is basically the same as Example 1, except that the current during printing is 25 mA.
[0049] Example 7: This example is basically the same as Example 1, except that the current during printing is 35 mA.
[0050] Embodiment 8: In terms of weight, the printing powder is prepared by mixing 7 parts of copper-chromium-niobium coarse powder and 3 parts of modified copper-chromium-niobium fine powder. The modified copper-chromium-niobium fine powder and the copper-chromium-niobium coarse powder are mixed by a powder mixer for 10 hours. The particle size of the copper-chromium-niobium coarse powder is 140-220 meshes, and the particle size of the modified copper-chromium-niobium fine powder is 220-270 meshes. The modification method of the modified copper-chromium-niobium fine powder comprises the following steps:
[0051] S1-1, dissolving copper sulfate in deionized water to obtain a copper sulfate solution; dissolving p-hydroxybenzoic acid in anhydrous ethanol to obtain a p-hydroxybenzoic acid solution; wherein the mass ratio of copper sulfate to deionized water is 1:12, and the mass ratio of p-hydroxybenzoic acid to anhydrous ethanol is 1:7;
[0052] S1-2, mixing the copper sulfate solution and the p-hydroxybenzoic acid solution in a mass ratio of 1:1, stirring evenly to obtain a mixed solution;
[0053] S1-3, adding ammonia water to the mixed solution, adjusting the pH value of the mixed solution to 8, then adding copper, chromium and niobium fine powders to the mixed solution in an amount of 4 times its own weight, and heating the mixed solution. During the heating process, the mixed solution is subjected to ultrasonic treatment, the initial frequency of the ultrasonic treatment is 22kHz, and the frequency of the ultrasonic treatment is increased by 2kHz for every 8°C increase in the temperature of the mixed solution, until the temperature of the mixed solution reaches 65°C, and the mixture is kept warm for 22 hours; the mass concentration of the ammonia water is 23%;
[0054] S1-4, after the ultrasonic treatment is completed, the mixed solution is filtered to obtain solid particles, and the solid particles are washed and dried to obtain the modified copper, chromium and niobium fine powder; the drying temperature is 180°C;
[0055] During printing, whenever the temperature of the powder in the electron beam focal area exceeds 1080°C, the electron beam is switched to intermittent irradiation. When the temperature of the powder in the electron beam focal area is lower than 960°C, the electron beam is switched to continuous irradiation.
[0056] The irradiation time T of the intermittent irradiation and the interval time T of the intermittent irradiation 1 The following relationship is met:
[0057]
[0058] Among them, m 1 is the mass of the modified copper-chromium-niobium fine powder. In this embodiment, m 1 The value is 30g, m is the total mass of the printing powder, in this embodiment, m is 100g, and in this embodiment, T 1 The value is 4ms.
[0059] Example 9: This example is basically the same as Example 8, except that, by weight, the printing powder is a mixture of 6 parts of copper-chromium-niobium coarse powder and 2 parts of modified copper-chromium-niobium fine powder.
[0060] Example 10: This example is basically the same as Example 8, except that, by weight, the printing powder is a mixture of 8 parts of copper-chromium-niobium coarse powder and 4 parts of modified copper-chromium-niobium fine powder.
[0061] Example 11: This example is basically the same as Example 8, except that the copper sulfate solution and the p-hydroxybenzoic acid solution are mixed in a mass ratio of 1:0.8.
[0062] Example 12: This example is basically the same as Example 8, except that the copper sulfate solution and the p-hydroxybenzoic acid solution are mixed in a mass ratio of 1:1.2.
[0063] Example 13: This example is basically the same as Example 8, except that the initial frequency of the ultrasonic treatment is 20 kHz.
[0064] Example 14: This example is basically the same as Example 8, except that the initial frequency of the ultrasonic treatment is 25 kHz.
[0065] Example 15: This example is basically the same as Example 8, except that the frequency of the ultrasonic treatment increases by 1 kHz for every 5°C increase in the temperature of the mixed solution.
[0066] Example 16: This example is basically the same as Example 8, except that the frequency of the ultrasonic treatment increases by 3 kHz for every 10°C increase in the temperature of the mixed solution.
[0067] Example 17: This example is basically the same as Example 8, except that whenever the temperature of the powder in the electron beam focal area exceeds 1380°C, the electron beam is switched to intermittent irradiation.
[0068] Example 18: This example is basically the same as Example 8, except that whenever the temperature of the powder in the electron beam focal area exceeds 1420°C, the electron beam is switched to intermittent irradiation.
[0069] Example 19: This example is basically the same as Example 8, except that T 1 The value is 2ms.
[0070] Example 20: This example is basically the same as Example 8, except that T 1 The value is 6ms.
[0071] Comparative Example 1: Taking Example 8 as a reference, the modified copper-chromium-niobium fine powder was replaced with ordinary copper-chromium-niobium fine powder.
[0072] Comparative Example 2: Taking Example 8 as a reference, the frequency of ultrasonic treatment was maintained at 22 kHz and did not change.
[0073] Comparative Example 3: Taking Example 8 as a reference, the electron beam was continuously irradiated during the printing process.
[0074] Comparative Example 4: Taking Example 8 as a reference, the irradiation time T of the intermittent irradiation is 4 ms.
[0075] Experimental Example: In order to explore the influence of the parameters of each embodiment on the performance of the heat dissipation housing, the heat dissipation housings prepared in each embodiment were subjected to performance tests, and the heat dissipation housing of embodiment 1 was subjected to metallographic tests. Figure 1 As shown in the figure, dark chromium-niobium phase agglomeration can be seen. The mechanical properties of the copper alloy are effectively improved by the agglomeration of chromium-niobium phases. The specific exploration is as follows:
[0076] Experimental Example 1: Investigating the influence of printing parameters on the performance of heat dissipation housing
[0077] Using Examples 1 to 8 as experimental comparison, the heat dissipation housing performance under different printing parameters is shown in Table 1 below:
[0078] Table 1 Heat dissipation housing performance under different printing parameters
[0079] Group Tensile strength / MPa Thermal conductivity W / (m·k) Example 1 334 336.5 Example 2 338 325.3 Example 3 353 308.6 Example 4 311 340.8 Example 5 332 331.5 Example 6 348 317.9 Example 7 325 333.7
[0080] It can be seen from the data in Table 1 that, compared with Examples 1, 2, 3, 4, 5, 6, and 7: too high or too low substrate preheating temperature, too high or too low electron beam scanning speed, and too high or too low current during printing will all lead to a decrease in the tensile strength or thermal conductivity of the heat dissipation housing, and too high tensile strength of the heat dissipation housing will lead to a decrease in thermal conductivity. Among them, the tensile strength and thermal conductivity of Example 1 are more moderate, so the printing parameters selected in Example 1 are optimal.
[0081] Experimental Example 2: Investigating the effect of modification on the performance of the heat dissipation housing
[0082] Using Examples 1 and 8 as experimental comparative examples, the heat dissipation housing performance under different printing powders is shown in Table 2 below:
[0083] Table 2 Heat dissipation shell performance under different printing powders
[0084] Group Tensile strength / MPa Thermal conductivity W / (m·k) Example 1 334 336.5 Example 8 370 340.2
[0085] It can be seen from the data in Table 2 that compared with Example 8, Example 1 has a significantly increased tensile strength of the heat dissipation shell after modification, while the thermal conductivity has not significantly decreased. This may be because the modified printing powder has a higher electron beam absorption efficiency and the heat dissipation shell has the least defects after molding. Therefore, the printing powder selected in Example 8 is better.
[0086] Experimental Example 3: Investigating the effect of printing powder ratio on the performance of heat dissipation housing
[0087] Using Examples 8 to 10 and Comparative Example 1 as experimental comparisons, the heat dissipation housing performance under different printing powder ratios is shown in Table 3 below:
[0088] Table 3 Heat dissipation shell performance under different proportions of printed powder
[0089] Group Tensile strength / MPa Thermal conductivity W / (m·k) Example 8 370 340.2 Example 9 356 336.1 Example 10 361 332.8 Comparative Example 1 342 338.5
[0090] It can be seen from the data in Table 3 that, compared with Examples 8, 9, and 10, the heat dissipation shell of Example 8 has the highest tensile strength and the highest thermal conductivity, indicating that the heat dissipation shell of Example 8 has the highest strength and the best thermal conductivity. This may be because under the printing powder ratio of Example 8, the heat dissipation shell structure is the densest, and the molten pool temperature is appropriate during printing, so the printing powder ratio of Example 8 is optimal.
[0091] Compared with Comparative Example 1, Example 8 shows that the tensile strength of the heat dissipation shell is significantly reduced after the copper, chromium and niobium fine powders are not modified. This may be because the printed powder has a lower absorption rate for electron beams and more defects in the heat dissipation shell after the modification. Therefore, the printing method of Example 8 is better.
[0092] Experimental Example 4: Investigating the influence of modification processing parameters on the performance of heat dissipation housing
[0093] Using Example 8, Examples 11 to 16 and Comparative Example 2 as experimental comparisons, the heat dissipation housing performance under different modification treatment parameters is shown in Table 4 below:
[0094] Table 4 Heat dissipation shell performance under different modification treatment parameters
[0095] Group Tensile strength / MPa Thermal conductivity W / (m·k) Example 8 370 340.2 Embodiment 11 358 332.4 Example 12 362 328.7 Embodiment 13 350 329.6 Embodiment 14 348 337.3 Embodiment 15 347 334.5 Example 16 355 323.6 Comparative Example 2 337 330.2
[0096] It can be seen from the data in Table 4 that, compared with Examples 8, 11, and 12, the heat dissipation housing of Example 8 has the highest tensile strength and the highest thermal conductivity, indicating that the heat dissipation housing of Example 8 has the highest strength and the best thermal conductivity. This may be because the modification effect of the copper chromium niobium fine powder is the best under the ratio of the copper sulfate solution to the p-hydroxybenzoic acid solution in Example 8, so the ratio of the copper sulfate solution to the p-hydroxybenzoic acid solution selected in Example 8 is optimal;
[0097] Compared with Examples 8, 13, 14, 15, and 16: too high or too low initial frequency of ultrasonic treatment, too high or too low change in ultrasonic treatment frequency will lead to reduced tensile strength and thermal conductivity of the heat dissipation housing. This may be because at the frequency of ultrasonic treatment in Example 8, the copper, chromium, and niobium fine powders can be fully dispersed, and the copper ion / parahydroxybenzoic acid coordination polymer can be fully loaded. Therefore, the initial frequency of ultrasonic treatment and the change in ultrasonic treatment frequency selected in Example 8 are both optimal;
[0098] Compared with Comparative Example 2, Example 8 shows that after the frequency of ultrasonic treatment does not change, the tensile strength of the heat dissipation shell is significantly reduced. This may be because the frequency of ultrasonic treatment does not change, resulting in the inability of the copper chromium niobium fine powder to fully load the copper ion / parahydroxybenzoic acid coordination polymer. Therefore, the modification treatment method selected in Example 8 is better.
[0099] Example 5: Investigating the influence of printing parameters on the performance of the heat dissipation housing
[0100] Using Example 8, Examples 17 to 20 and Comparative Examples 3 to 4 as experimental comparisons, the heat dissipation housing performance under different printing parameters is shown in Table 5 below:
[0101] Table 5 Heat dissipation housing performance under different printing parameters
[0102] Group Tensile strength / MPa Thermal conductivity W / (m·k) Example 8 370 340.2 Embodiment 17 362 338.9 Embodiment 18 354 332.3 Embodiment 19 357 333.4 Embodiment 20 363 330.3 Comparative Example 3 333.1 328.2 Comparative Example 4 336.2 327.8
[0103] Compared with Examples 8, 17, and 18: the heat dissipation shell of Example 8 has the highest tensile strength and the highest thermal conductivity, indicating that the heat dissipation shell of Example 8 has the highest strength and the best thermal conductivity. This may be because at the powder temperature in the electron beam focal area selected in Example 8, the powder can be fully melted to form a molten pool, so the powder temperature in the electron beam focal area selected in Example 8 is optimal;
[0104] Compared with Examples 8, 19, and 20: the heat dissipation shell of Example 8 has the highest tensile strength and the highest thermal conductivity, indicating that the heat dissipation shell of Example 8 has the highest strength and the best thermal conductivity. This may be because under the interval time selected in Example 8, the cooling rate of the molten pool is appropriate and the internal stress is less, so the interval time selected in Example 8 is optimal;
[0105] Example 8 is compared with Comparative Examples 3 and 4: The electron beam is continuously irradiated or the irradiation time T and the interval time T 1 The same will lead to a decrease in the tensile strength of the heat dissipation shell. This may be due to the continuous irradiation of the electron beam or the irradiation time being too long, which will cause the molten pool temperature to be too high, resulting in more defects inside the heat dissipation shell.
Claims
1. A method for electron beam printing a copper-chromium-niobium heat dissipation housing, characterized in that: The following steps are involved: S1. Take 140-270 mesh copper-chromium-niobium powder as printing powder; S2, adding printing powder into the building chamber of the electron beam printing device, preheating the substrate, the substrate preheating temperature is 560-600° C., and the preheating time is 25-35 seconds; S3, after preheating is completed, printing begins layer by layer. The electron beam scanning speed during printing is 3200-3600 mm / s, the current is 25-35 mA, and the printing layer thickness is 0.05-0.5 mm. After printing is completed, a blank is obtained; S4, turning and polishing the blank to obtain a heat dissipation shell.
2. The method for electron beam printing of copper-chromium-niobium heat dissipation housing according to claim 1, characterized in that: In step S4, an electron beam is used to preheat the powder for each printing layer, and the current of the preheating electron beam is 45-50 mA.
3. The method for electron beam printing a copper-chromium-niobium heat dissipation housing according to claim 2, characterized in that: In step S2, the printing powder is dried at 160-200° C. for 10-14 h before being added to the building chamber.
4. The method for electron beam printing a copper-chromium-niobium heat dissipation housing according to claim 1, characterized in that: In step S4, the turning processing amount is 0.8-1.2 mm.
5. The method for electron beam printing a copper-chromium-niobium heat dissipation housing according to claim 1, characterized in that: In step S4, a sandblasting process is used during polishing.
Citation Information
Cited By
Method for manufacturing aerospace component through 3D printing and aerospace component
CN122462556A